Enhancing Early Childhood Social Development: An Analysis Through the Lens of Multicultural Education - Anisa, Clera Agretyas Nur; Kristiana, Dian; Rusdiani, Nurtina Irsad; Kusmiati, Ami (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Social development is a critical aspect of early childhood growth. This study aims to analyse the social development of children aged 5–6 years and the supporting and inhibiting factors from the perspective of multicultural education. The research employed a qualitative approach with a case study design. Data were collected through interviews with teachers, classroom observations in early childhood education (PAUD), and documentation. The data analysis process focused on three stages: data reduction, data presentation, and conclusion drawing or verification. The findings revealed that the social development of 2 out of 6 children aged 5–6 years was categorized as Developing as Expected (BSH), while the other 4 children were in the Beginning to Develop (MB) category. Children’s social competencies are interrelated; weaknesses in one social competency can influence others. Inhibiting factors in the implementation of education include parents, children, and teachers, while supporting factors involve parents, peers, and teachers. Thus, multicultural education plays a strategic role in optimizing the social development of early childhood learners.